Korelasi kadar hemoglobin dengan saturasi oksigen pada guru besar Universitas Padjadjaran - Della Suherlim; Leonardo Lubis; Hikmat Permana (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2018)
Background: The aging process is recognizable through bodily functions dicreases caused by molecular and cellular damage. Elderly is the most affected population by this aging process, such as the majority of professors in Universitas Padjadjaran. In elderly, that tissue oxigenation is trend to decrease due to reduction of both hemoglobin level and oxygen saturation. Aim: This study aimed to find out correlation between hemoglobin level and oxygen saturation in the elderly professors of Universitas Padjadjaran. Method: This study analyzed secondary data from health check-up result of the professors. 108 data of the professors met the inclusion criteria and were used in this study. This data underwent the normality test ( Male = 84 subjects, using the Kolmogorov-Smirnov test. Female = 24 subjects, using Shapiro-Wilk test.). Spearman’s Rank correlation test was used for total subjects and male professors group, while Pearson correlation test was used for female professors group. Results: Correlation test between hemoglobin concentration and oxygen saturation resulted in an insignificant result in male professors (r = 0.028 ; p = 0.801; z = 0.200 ; 0.00 ), female professors (r = 0.132; p = 0.538; z = 0.582; 0.272), and also in total subjects (r = 0.036; p = 0.712; z = 0.200; 0.00 ). Conclusion: There is no correlation between hemoglobin concentration and oxygen saturation in the elderly professors of Universitas Padjadjaran.